The impact of non-oil economic determinants on Saudi economic growth - Mohammed, AbuAlQasim Abbas (Journal of Economic, Administrative and Legal Sciences, 2024)
This study examined the impact of non-petroleum economic determinants on Saudi economic growth, and focused on several variables as the most important determinants of these activities and aimed to measure the effect of these determinants as explanatory variables (agricultural activity, mining, financial and insurance services) on economic growth as a dependent variable. The study concluded that mining, and financial and insurance services, respectively, are the explanatory variables that have a significant and real impact on the dependent variable (economic growth) as they are correlated with relationship that varies from each other with the dependent variable and suggested that the mining variable is the variable that has a high explanatory ability on economic growth. The most important recommendations were made: increasing the effectiveness of the mining sector by expanding, increasing detection, improving the environment, raising the efficiency of the infrastructure associated with the sector, developing the mining sector and increasing production for this sector to meet global demand, raising exports and increasing revenues to achieve leadership and raise the level of global competitiveness.